2018
DOI: 10.5815/ijem.2018.03.05
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation on the Micro Structural and Elemental Composition of Sugarcane Bagasse Ash Blended Concrete using SEM and EDS Technique

Abstract: Sugarcane bagasse ash (SBA) is a solid waste obtained from the boilers of sugar factories after the combustion of sugarcane bagasse. Sugarcane bagasse ash mainly consists of amorphous silica and can be used as a supplementary cementitious material in the production of concrete. In the present study, the physical properties of sugarcane bagasse ash, namely, particle size distribution, surface area, specific gravity, morphology and chemical properties like elemental composition of SBA and ordinary Portland cemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…Li et al (2022) revealed the mechanism of salt and frost deterioration of wind-cured sand concrete using the SEM technique. Patil et al (2018) studied the microstructure of bagasse ash concrete with SEM technology. Khonsari et al (2018) revealed the effect of swollen perlite aggregates on the number, shape, and distribution of concrete pores by SEM images.…”
Section: Open Accessmentioning
confidence: 99%
“…Li et al (2022) revealed the mechanism of salt and frost deterioration of wind-cured sand concrete using the SEM technique. Patil et al (2018) studied the microstructure of bagasse ash concrete with SEM technology. Khonsari et al (2018) revealed the effect of swollen perlite aggregates on the number, shape, and distribution of concrete pores by SEM images.…”
Section: Open Accessmentioning
confidence: 99%